Drug-Induced Dynamics of Bile Colloids - Hanio, Simon; Schlauersbach, Jonas; Lenz, Bettina; Spiegel, Franziska; Böckmann, Rainer; Schweins, Ralf; Nischang, Ivo; Schubert, Ulrich S.; Endres, Sebastian; Pöppler, Ann Christin; Brandl, Ferdinand P.; Smit, Theo M.; et al. (Langmuir, 2021)
Bile colloids containing taurocholate and lecithin are essential for the solubilization of hydrophobic molecules including poorly water-soluble drugs such as Perphenazine. We detail the impact of Perphenazine concentrations on taurocholate/lecithin colloids using analytical ultracentrifugation, dynamic light scattering, small-angle neutron scattering, nuclear magnetic resonance spectroscopy, coarse-grained molecular dynamics simulations, and isothermal titration calorimetry. Perphenazine impacted colloidal molecular arrangement, structure, and binding thermodynamics in a concentration-dependent manner. At low concentration, Perphenazine was integrated into stable and large taurocholate/lecithin colloids and close to lecithin. Integration of Perphenazine into these colloids was exothermic. At higher Perphenazine concentration, the taurocholate/lecithin colloids had an approximately 5-fold reduction in apparent hydrodynamic size, heat release was less exothermic upon drug integration into the colloids, and Perphenazine interacted with both lecithin and taurocholate. In addition, Perphenazine induced a morphological transition from vesicles to wormlike micelles as indicated by neutron scattering. Despite these surprising colloidal dynamics, these natural colloids successfully ensured stable relative amounts of free Perphenazine throughout the entire drug concentration range tested here. Future studies are required to further detail these findings both on a molecular structural basis and in terms of in vivo relevance.
CRIS-Team Scopus Importer:2021-03-05